MINAT PETANI DALAM PENGEMBANGAN KAWASAN RUMAH PANGAN LESTARI (KRPL) SISTEM VERTIKULTUR DI KECAMATAN CILAKU KABUPATEN CIANJUR PROVINSI JAWA BARAT - Irsan Setiawan; Dedy Kusnadi; Harniati Harniati (Jurnal Inovasi Penelitian, 2020)
Chavi District has abundant natural resource potential. The availability of various types of food and spices, however, the realization of public consumption is still below the recommended nutritional fulfillment. This Chavi District has abundant natural resource potential. The availability of various types of food and spices, however, the realization of public consumption is still below the recommended nutritional fulfillment. This study aims to describe the interests of farmers, analyze the factors that affect farmers 'interests, and formulate strategies to increase farmers' interests. This research was conducted in Chavi Subdistrict, Cianjur Regency on March 7 to June 30, 2020. The research sample was 62 farmers taken using purposive sampling technique. Data analysis techniques used were descriptive analysis, multiple linear regression analysis and Kendall's W. analysis. farmer characteristics, facilities and infrastructure, and extension activities. The results showed that the interest of farmers in developing sustainable food house areas in the verticulture system in Chavi District, Cianjur Regency was still in the medium category with a percentage (51.61%), so it needed to be improved. The factors that influence the interest of farmers are length of education and area of ​​yard. Strategies to increase farmer interest include increasing farmer involvement, extension methods through demonstration of methods and plot demonstrations, as well as extension materials and media.